Protracted bacterial bronchitis: reinventing an old disease. Issue 1 (22nd November 2012) - Craven, Vanessa; Everard, Mark L
Abstract : Chronic cough is common in the paediatric population, yet the true prevalence of this condition remains difficult to define. Protracted bacterial bronchitis (PBB) is a disease caused by the chronic infection of the conducting airways. In many children the condition appears to be secondary to impaired mucociliary clearance that creates a niche for bacteria to become established, probably in the form of biofilms. In others, immunodeficiencies, which may be subtle, appear to be a factor. PBB causes persistent coughing and disturbed sleep, and affects exercise tolerance, causing significant levels of morbidity. PBB has remained largely unrecognised and is often misdiagnosed as asthma.